Social Interaction and The Practice of Power Among Small Fishers - Asnika Putri Simanjuntak; Titik Sumarti; Rilus A Kinseng (Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Relations between humans and social groups always involve power. Power exists in all fields of life; it includes the ability to govern and also make decisions that directly influence the actions of others. This study aims to determine how social interaction and power practices between the crew and shipowner; and between crews on small vessels. This research was conducted with a descriptive-qualitative approach using a case study strategy. The study was conducted in Muarareja Urban Village, West Tegal Subdistrict, Tegal City, Central Java Province. The results showed that small scale fishers in Muarareja Urban Village, Tegal City can be categorized as daily fishers and weekly fishers. The practice of power between the owner and the daily crew on the small vessels has an exploitative relationship dimension. This relationship is indicated by the compulsion of the shipowner to the crew to keep fishing even though the weather is bad or during a low season. The practice of power between the shipowner and the crew was strongly influenced by the shipowner's debt to the Bank or middleman, which must be paid every month. On the other hand, the practice of power exercised by the weekly fishers to the shipowner is by being able to resign and choose to work with other shipowners easily. If the crew feels uncomfortable working on a ship, they will look for a new shipowner.